Discrimination analysis of breast calcifications using x-ray dark-field radiography - Rauch, Thomas; Rieger, Jens; Pelzer, Georg; Horn, Florian; Erber, Ramona; Wunderle, Marius; Emons, Julius; Nabieva, Naiba; Fuhrich, Nicole; Michel, Thilo; Hartmann, Arndt; Fasching, Peter; et al. (Medical Physics, 2020)
Background X-ray dark-field radiography could enhance mammography by providing more information on imaged tissue and microcalcifications. The dark field signal is a measure of small angle scattering and can thus provide additional information on the imaged materials. This information can be useful for material distinction of calcifications and the diagnosis of breast cancer by classifying benign and malign association of these calcifications.
CRIS-Team WoS Importer:2020-03-06

Intrinsic limits on resolutions in muon- and electron-neutrino charged-current events in the KM3NeT/ORCA detector - Adrian-Martinez, S.; Ageron, M.; Aiello, S.; Albert, A.; Ameli, F.; Anassontzis, E. G.; Andre, Michel; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Avgitas, T.; et al. (Journal of High Energy Physics, 2017)
Studying atmospheric neutrino oscillations in the few-GeV range with a multimegaton detector promises to determine the neutrino mass hierarchy. This is the main science goal pursued by the future KM3NeT/ORCA water Cherenkov detector in the Mediterranean Sea. In this paper, the processes that limit the obtainable resolution in both energy and direction in charged-current neutrino events in the ORCA detector are investigated. These processes include the composition of the hadronic fragmentation products, the subsequent particle propagation and the photon-sampling fraction of the detector. GEANT simulations of neutrino interactions in seawater produced by GENIE are used to study the effects in the 1-20 GeV range. It is found that fluctuations in the hadronic cascade in conjunction with the variation of the inelasticity y are most detrimental to the resolutions. The effect of limited photon sampling in the detector is of significantly less importance. These results will therefore also be applicable to similar detectors/media, such as those in ic
Keywords: Neutrino Detectors and Telescopes (experiments)